ADOPTION OF COMPRESSED NATURAL GAS (CNG) AND COMPRESSED BIOMETHANE GAS (CBG) AS ENERGY AND TRANSPORT FUELS IN NIGERIA: A REVIEW OF SAFETY, BENEFITS, AND IMPLEMENTATION STRATEGIES - muhibbudin, ismail (Program Vokasi-Universitas Negeri Gorontalo, 2025)
The removal of fuel subsidies in Nigeria has heightened energy and transportation costs, intensifying inflationary pressures and economic instability. To address this, adopting alternative fuels particularly Compressed Natural Gas (CNG) and Compressed Biomethane Gas (CBG) offers a pathway toward energy diversification and resilience. This review systematically synthesizes academic and technical literature, including 45 studies published between 2010 and 2024, to assess the safety, environmental, economic, and energy security implications of transitioning from petroleum fuels to CNG and CBG. Findings reveal that while CBG provides superior environmental benefits and long-term sustainability, CNG remains more cost-effective for short-term implementation. The study identifies policy, infrastructure, and technological gaps limiting adoption and concludes with targeted recommendations to guide Nigeria’s sustainable energy transition strategy.